Communicating salt reduction strategies in Malaysia: a monograph - Mohamed, Shafizan (Communication and Media Centre (COMET), KIRKHS, IIUM, 2024)
The genesis of this monograph traces back to a fundamental recognition—the pressing need to address the pervasive impact of excessive salt intake on public health in Malaysia. In the pursuit of optimal health outcomes, the exploration of innovative and effective salt reduction strategies becomes imperative. Thus, this monograph provides a comprehensive overview of the salt reduction landscape in Malaysia. It navigates through the initial challenges faced by the Salt Reduction Strategy, explores the evolution of communication and behavioural change initiatives, and delves into the intricacies of formulating, operationalizing, and assessing behavioural objectives. By encapsulating a broad spectrum of research findings, theoretical frameworks, and practical strategies, this document aspires to serve as a valuable resource for policymakers, health professionals, researchers, and stakeholders invested in the pursuit of a healthier, salt-aware Malaysia.